2018
DOI: 10.1177/2047487318807767
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality is increased in patients with undetected prediabetes and type-2 diabetes hospitalized for worsening heart failure and reduced ejection fraction

Abstract: Background: We assessed the prevalence of newly diagnosed prediabetes and type-2 diabetes mellitus (T2DM), and their impact on long-term mortality in patients hospitalized for worsening heart failure with reduced ejection fraction (HFrEF). Methods: We included patients hospitalized with HFrEF and New York Heart Association (NYHA) functional class II-III. Baseline two-hour oral glucose tolerance test was used to classify patients as normoglycaemic or having newly diagnosed prediabetes or T2DM. Outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
1
28
0
5
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) is common (∼20-40%) in patients with heart failure (HF), 1 and is associated with worse symptoms and quality of life, a greater burden of HF hospitalisation, and higher mortality rates compared to patients without T2DM. [2][3][4][5][6][7] Increased levels of glycosylated haemoglobin (HbA 1c ) have been associated with increased morbidity and mortality in patients with T2DM and HF not receiving treatment with glucose-lowering drugs. 8,9 However, once treatment of T2DM has been initiated, this relationship may no longer be linear.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is common (∼20-40%) in patients with heart failure (HF), 1 and is associated with worse symptoms and quality of life, a greater burden of HF hospitalisation, and higher mortality rates compared to patients without T2DM. [2][3][4][5][6][7] Increased levels of glycosylated haemoglobin (HbA 1c ) have been associated with increased morbidity and mortality in patients with T2DM and HF not receiving treatment with glucose-lowering drugs. 8,9 However, once treatment of T2DM has been initiated, this relationship may no longer be linear.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) and type 2 diabetes mellitus (T2DM) commonly coexist, and T2DM is a recognized risk factor for thromboembolism in patients with AF . In the general population, T2DM has been associated with an increased risk of heart failure (HF) and mortality independently of other clinical characteristics . Specifically, in patients with AF, the impact of T2DM is less well established concerning complications beyond stroke and systemic embolism.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the general population, T2DM has been associated with an increased risk of heart failure (HF) and mortality independently of other clinical characteristics. [3][4][5][6] Specifically, in patients with AF, the impact of T2DM is less well established concerning complications beyond stroke and systemic embolism. Available data are conflicting, since several studies have suggested higher risks of all-cause mortality, [7][8][9] HF events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting separately prediabetes and newly diagnosed T2DM is one of the most important strengths of the data. 1 To the best of our knowledge, this is the first study to report the prevalence of prediabetes in a real-life observational cohort of consecutive patients hospitalized for worsening HF. Previously, three RCTs enrolling HFrEF patients [10][11][12] have reported a lower prevalence of prediabetes, but all of these studies included ambulatory HF patients (Figure 1).…”
mentioning
confidence: 95%
“…This article refers to 'Long-term mortality is increased in patients with undetected prediabetes and type 2 diabetes hospitalized for worsening heart failure and reduced ejection fraction' by Pavlovic´and colleagues, published in this issue of the journal. 1 The syndrome of heart failure (HF) is the clinical manifestation of diverse underlying cardiac and noncardiac comorbidities, resulting in a heterogeneous patient population ranging from stable and ambulatory to decompensated and hospitalized. 2 Among patients recently hospitalized for worsening HF, the mortality and readmission rates approach 27% and 44%, respectively, at 1 year.…”
mentioning
confidence: 99%